Treatment for patients with symptomatic tunneled coronary arteries - Gogayeva, O. (Ukrainian Journal of Cardiovascular Surgery, 2019)
The article focuses on the treatment of abnormal coronary artery location, so-called tunnelled coronary artery (TCA). Objective: to show our experience in treatment of symptomatic patients with TCA taking into account the mechanism of ischemia development. To evaluate efficacy of different treatment methods and to show our algorithm of treatment for patients with TCA. Material and methods: Over 13 years, we observed 347 patients with symptomatic TCA diagnosed during coronary an-giography. The following clinical examinations were performed for all patients: ECG, echocardiography, and coronary an-giography Results: Misunderstandings of myocardial ischemia causes during myocardial bridging (MB) occurs primarily when physicians underestimate the clinical significance of this anomaly. In our opinion, one of the factors causing myocardial ischemia during MB is diastolic dysfunction, which leads to the prolongation of systolic compression at the first phase of di-astole. There are the following methods of treatment of symptomatic patients with TCA: drug therapy, stenting of a tunnelled segment and surgical correction. The method of treatment for patients was determined strictly on an individual basis, taking into account the length of a tunnelled segment of the coronary artery, the degree of systolic compression of the coronary ar-tery and the presence of concomitant cardiac diseases. Despite the safety and efficacy of endovascular treatment, indications for this minimally invasive method should only be performed in cases of patients who are resistant to drug therapy and have an unextended (<15 mm) tunnelled segment of the coronary artery. Long-term results of different types of treatment were mostly good in patients with symptomatic TCA for a period of 12 months to 13 years. All patients show significant improve-ment in their health condition. An individual approach in treating patients with this anomaly helps to avoid life-threatening events and to improve quality of life for patients with this anomaly.